Paleocene‐Eocene foreland basin evolution in the Himalaya of southern Tibet and Nepal: Implications for the age of initial India‐Asia collision. Issue 5 (27th May 2014) - DeCelles, P. G.; Kapp, P.; Gehrels, G. E.; Ding, L.
Abstract Siliciclastic sedimentary rocks derived from the southern Lhasa terrane, sitting depositionally upon rocks of the northern Indian passive continental margin, provide an estimate of the age of initial contact between the continental parts of the Indian and Asian plates. We report sedimentological, sedimentary petrological, and geochronological data from Upper Cretaceous‐Paleocene strata in the Sangdanlin section, located along the southern flank of the Indus‐Yarlung suture zone in southern Tibet. This is probably the most proximal, and therefore the oldest, record of the India‐Asia collision. These strata were deposited by high‐density turbidity currents (or concentrated density flows) and suspension settling of pelagic biogenic debris in a deep‐marine setting. An abrupt change from quartz‐arenitic to feldspatholithic sandstone compositions marks the transition from Indian to Asian sediment provenance. The abrupt compositional change is accompanied by changes in U‐Pb ages of detrital zircons diagnostic of a sediment provenance reversal, from Indian to Asian sources. The timing of the transition is bracketed between 60 Ma and 58.5 ± 0.6 Ma by detrital zircon U‐Pb ages and zircon U‐Pb ages from a tuffaceous bed in the upper part of the section. In the context of a palinspastically restored regional paleogeographic framework, data from the Sangdanlin section combined with previously published data from the northern Tethyan Himalaya and the frontal Nepalese Lesser Himalaya and Subhimalaya suggest that a flexural wave migrated 1300 km southward across what is now the Himalayan thrust belt from Paleocene time to the present.